Analisis Penilaian Kesehatan Bank Dengan Menggunakan Metode RGEC (Risk, Profile, Good Corporate Governance, Earning, Capital) Pada Bank Umum Syariah Tahun 2017-2021 - Dayyesi, Hermika; Rafidah, Rafidah; Siregar, Erwin Saputra (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2023)
This study aims to determine the soundness of Islamic Commercial Banks in 2017-2021 by using the measurement method regulated in Bank Indonesia Regulation, PBI No. 13/1/PBI/2011 through the RGEC method is a Risk Profile using credit risk (NPF), liquidity risk (FDR), Earnings (ROA and NIM), and Capital (CAR). In Good Corporate Governance research using data that has been processed and obtained from each Islamic bank. The object of this research is all Islamic Commercial Banks. The sample in this study used purposive sampling. This study uses a quantitative approach sourced from financial reports through the official websites of each Islamic Commercial Bank and OJK. The data used is Time Series data for 2017-2021. Analyzed using Microsoft Excel and formulas in ratios. Based on the results of this study, it shows that the health of commercial banks in terms of the Risk Profile aspect with the ratio of NPF and FDR during 2017-2021 is in a healthy condition, in terms of the GCG aspect of Islamic commercial banks in 2017-2021 is in a healthy condition, in terms of aspects Erning with ROA and NIM ratios for Islamic commercial banks in 2017-2021 is in a very healthy condition, in terms of Capital aspect with CAR ratios for Islamic commercial banks in 2017-2021 in very healthy condition.